More absolute moderate-to-vigorous physical activity is associated with better health-related quality of life in outpatients with an acquired brain injury - MacDonald, Emily E.; Pellerine, Liam P.; Miller, Katerina E.; Frayne, Ryan J.; O’Brien, Myles W. (Frontiers in Rehabilitation Sciences, 2024)
Health-related quality of life (HRQoL) is a patient-perceived measure of physical, social, and emotional health. Acquired brain injury (ABI) occurs due to damage to the brain after birth. Individuals with an ABI typically present with reduced HRQoL and require additional support to maintain their HRQoL. Although structured exercise training has been shown to improve HRQoL in individuals with ABI, there is little research on habitual, real-world activity. Most activity research characterizes moderate-to-vigorous physical activity (MVPA) in absolute terms; however, relative physical activity levels have been promoted for research in clinical populations. We tested whether longer MVPA durations, measured in absolute/relative levels, are associated with higher HRQoL in outpatients with ABIs. In total, 26 adults (54 ± 13 years, 16 females) with ABI completed the Quality of Life After Brain Injury questionnaire, a 6-min walk test (a measure of aerobic fitness; 490 ± 105 m), and wore an activPAL device 24 h/day for 7 days. Participants had an average HRQoL score of 53.4 ± 15.0 (out of 100), with 20 of 26 showing impaired HRQoL (score <60). Absolute MVPA (74.6 ± 91.0 min/week, b = 0.09, p = 0.03) was associated with HRQoL, whereas total physical activity (565.7 ± 264.8 min/week, p = 0.47), light physical activity (LPA; 491.1 ± 224.3 min/week, p = 0.98), and step count (5,960 ± 3,037 steps/day, p = 0.24) were not. Neither relative LPA (521.4 ± 244.9) nor relative MVPA (33.5 ± 34.9 min/week) were associated with HRQoL (both p values > 0.14). Targeting more absolute MVPA, but not necessarily relative MVPA, may be an effective strategy for interventions aiming to improve HRQoL in individuals with ABI.